Linking smallholder producers to high-value markets through producer cooperatives: A case study of vegetable producer cooperatives in Cambodia - Tray B; Garnevska E; Shadbolt N (International Food and Agribusiness Management Association)
Modern retail markets have grown in Cambodia, but vegetable growers are unlikely to gain benefits from these high value markets (HVMs). Producer cooperatives (PCs) could play a critical role in linking smallholder farmers to HVMs. The purpose of this paper is: (1) to examine the role of PCs in linking vegetable producers to HVMs; and (2) analyse the factors affecting successful participation in HVMs. This study applied a mixed methods approach to PCs selling the members’ vegetables to HVMs (PC-HVMs), and PCs selling members’ vegetables to traditional markets (TMs) only (PC-TMs). Both groups of PCs provided services to their members (e.g. input, financial, extension services). However, the content and quality of these services were different. PC-TMs emphasised only on support linked to production, while PC-HVMs focused on both production and marketing support. This study indicated that vegetable farming experience, total vegetable produce, and average vegetable prices had a statistically significant influence on producers’ participation in HVMs. However, vegetable farm size showed a negatively significant effect on participation in HVMs. As one of the very few empirical studies on PCs in Cambodia the research provides valuable context for further studies. It has developed and tested a framework for analysing the factors affecting successful participation in HVMs and provides an explanation of why some PCs can successfully participate in HVMs.
Keywords: producer cooperatives; smallholder farmers; vegetables; high-value markets; Cambodia; 0701 Agriculture, Land and Farm Management